Identifikasi Senyawa Penghambat Enzim α-Glukosidase dari Ekstrak Etanol 96% Daun Yakon (Smallanthus sonchifolius [Poepp.& Endl.]H. Robinson) - Zuhelmi Aziz; Farhana Hanida Al Qisthi; Ratna Djamil; Nancy Dewi Yuliana; Partomuan Simanjuntak; Syamsudin Abdillah (JURNAL ILMU KEFARMASIAN INDONESIA, 2019)
The leaves of yacon (Smallanthussonchi folius [Poepp. &Endl.] H. Robinson) or in Indonesia known as “Daun insulin” (Insulin leaf), scientifically has various medicinal properties and one of them as antidiabetic. The aim of this research is to know α-glucosidase enzyme inhibitor compound in the ethanol 96% extract of yacon leaves. Fractionation of ethanol extract subjected to column chromatography (SiO2; dichloromethane-methanol-water = 5 : 5 : 1) gave 5 fractions (Fr -1 ~Fr – 5). The results of the -glucosidase enzyme inhibition activity test in vitro against the five fractions obtained the 3rd fraction as the most active of 87.84 %. Purification of the 3rd fraction with preparative thin layer chromatography (SiO2; n-BuOH-ethanol-water = 4 : 1 : 2.2) gave pure isolate as Fr 3-1. Identification of pure isolates Fr 3-1 was carried out by interpreted spectra of Ultraviolet, Fourier Transform-Infra Red, Mass Spectra (from LC-MS) and compared data on the chemical shift of the Nuclear Magnetic Resonance (proton and carbon) and determined as Nystose (GF3) compound. The results of the -glucosidase enzyme inhibition activity showed that Fr 3-1 has IC50 of 21.36 ppm